PF.60 Neonatal Hypophosphatasia: A Rare Disorder and New Treatment. (26th April 2013) - Hiremath, S; Kumar, VK Devendra; Padidela, R; Mughal, Z
Abstract : Hypophosphatasia is a rare inborn error of metabolism resulting from mutations in the gene for the tissue-nonspecific isozyme of alkaline phosphatase (TNSALP). There is deficiency of alkaline phosphatase activity leading to severe rickets/osteomalacia. Severely affected babies die from respiratory insufficiency. There is no licenced medical treatment available. We report a case diagnosed recently with hypophosphatasia who is receiving pioneering enzyme replacement treatment. Baby I was born at 34/40 and required ventilatory support from birth due to respiratory insufficiency. She was noted to have short limbs, hypotonia, and thin ribs on x-rays. Her serum alkaline phosphatase was low; urinary phosphoethanolamine and serum calcium were elevated confirming hypophosphatasia. In a recent multinational study of 11 patients with severe hypophosphatasia, treatment with recombinant human bone targeted TNSALP (ENB 0040) has been shown to improve bone mineralization. This was associated with healing of rickets, improved developmental milestones and pulmonary function. Under guidance from the regional Metabolic Bone team at Manchester and with parental consent, Baby I was commenced on ENB 0040 (Asfotase alfa) at the age of 4 weeks with subcutaneous injections three times a week. The drug is being offered to this infant on compassionate grounds by the manufacturer (Alexion pharmaceuticals). Within 6 weeks of treatment calcium requirement of infant has increased and X-rays have demonstrated remarkable improvement in mineralisation. She remains ventilator dependant with a tracheostomy in situ but, we anticipate that with ENB 0040 treatment, improvement in bone mineralisation and muscle function will facilitate weaning from ventilation.